Progesterone Receptor Signaling Selectively Modulates Cytokine-Induced Global Gene Expression in Human Cervical Stromal Cells - Kniss, Douglas A.; Summerfield, Taryn L. (Frontiers in Genetics, 2020)
Preterm birth (PTB) is the leading cause of morbidity and mortality in infants <1 year of age. Intrauterine inflammation is a hallmark of preterm and term parturition; however, this alone cannot fully explain the pathobiology of PTB. For example, the cervix undergoes a prolonged series of biochemical and biomechanical events, including extracellular matrix (ECM) remodeling and mechanochemical changes, culminating in ripening. Vaginal progesterone (P4) prophylaxis demonstrates great promise in preventing PTB in women with a short cervix (<25 mm). We used a primary culture model of human cervical stromal fibroblasts to investigate gene expression signatures in cells treated with interleukin (IL) in the presence or absence of P4 following 17estradiol (17E2) priming for 7-10 days. Microarrays were used to measure global gene expression in cells treated with cytokine or P4 alone or in combination, followed by validation of select transcripts by semi-quantitative polymerase chain reactions (qRT-PCR). Primary/precursor (MIR) and mature microRNAs (miR) were quantified by microarray and Nanostring platforms, respectively, and validated by qRT-PCR. Differential gene expression was computed after data normalization followed by pathway analysis using Kyoto Encyclopedia Genes and Genomes (KEGG), Panther, Gene Ontology (GO) and Ingenuity Pathway Analysis (IPA) upstream regulator algorithm tools. Treatment of fibroblasts with IL alone resulted in the differential expression of 1432 transcripts (protein coding and non-coding), while P4 alone lead to the expression of only 43 transcripts compared to untreated controls. Cytokines, chemokines and their cognate receptors and prostaglandin endoperoxide synthase-2 (PTGS-2) were among the most highly up-regulated transcripts following either ILor IL+P4. Other prominent differentially expressed transcripts were those encoding ECM proteins, ECM degrading enzymes and enzymes involved in glycosaminoglycan (GAG) biosynthesis. We also detected differential expression of bradykinin receptor-1 and -2 transcripts, suggesting (prominent in tissue injury/remodeling) a role for the kallikrein-kinin system in cervical responses to cytokine and/or P4 challenge. Collectively, this global gene expression study provides a rich database to interrogate stromal fibroblasts in the setting of a proinflammatory and endocrine milieu that is relevant to cervical remodeling/ripening during preparation for parturition.